Development of a predictive model of Crohn’s disease proximal small bowel involvement in capsule endoscopy evaluation - Rodrigues-Pinto, Eduardo; Cardoso, Helder; Rosa, Bruno; Santos-Antunes, João; Rodrigues, Susana; Marques, Margarida; Lopes, Susana; Albuquerque, Andreia; Carvalho, Pedro; Moreira, Maria; Cotter, José; Macedo, Guilherme (Endoscopy International Open, 2016)
Background and study aims: One of the indications for capsule endoscopy (CE) is the detection of proximal small bowel (SB) involvement in Crohn's disease (CD) patients. Our aim was to assess clinical, laboratory and endoscopic predictors associated with proximal SB involvement in CD patients submitted to CE. Patients and methods: Retrospective multicenter study in which Lewis score (LS) was systematically determined in 190 CE of patients diagnosed with CD between 2003 and 2014. Results: Significant inflammatory activity (LS > 135) was present in 23 % of the patients in the first tertile and in 31 % of the patients in the second tertile. Albumin, haemoglobin, and total proteins were significantly lower in patients with a LS > 790 compared to patients with a LS < 135, while white blood cell counts and C-reactive protein were significantly higher. In the univariable analysis, a higher risk for proximal SB involvement at CE was associated with ileal involvement at ileocolonoscopy (OR 2.858, P = 0.006), higher platelets levels (OR 1.005, P = 0.004) and significant weight loss (OR 2.450, P = 0.006). In logistic regression, ileal involvement at ileocolonoscopy (OR 6.817, P = 0.003), stricturing behavior (OR 8.653, P = 0.011) and significant weight loss (OR 3.629, P = 0.028) were independently associated with proximal SB involvement at CE. Considering the ROC curve of this model, a cut-off > 0.249 predicts proximal SB involvement with 90 % sensitivity and 40 % specificity (AUROC 0.732). Conclusions: One-third of patients had proximal SB involvement. Predictive factors were significant weight loss, stricturing behaviour, and ileal involvement at ileocolonoscopy. These data help to select CD patients that benefit the most from performing a CE.